Varying the Number of FOP Warnings on Hedonic and Utilitarian Food Products: Evidence from Chile. Issue 2 (12th February 2020) - Uribe, Rodrigo; Manzur, Enrique; Cornejo, Carolina
ABSTRACT: FOP food-labeling systems seek to inform on a product`s healthy/unhealthy state and signal a product`s healthiness level. Research in this area has focused primarily on exploring the healthy/unhealthy dimension, leaving the effect of FOP schemes on the perception of healthiness under-researched. The objective of this study is to evaluate how an increase or decrease in the number of warning signs in the packaging of food products affects the healthiness perception of the consumer and the subsequent purchase intention. This examination is developed by comparing utilitarian and utilitarian food products as a means to examine whether FOP labeling effects are moderated by prior buying motivations. Results show that a different number of warnings is correctly perceived and used by consumers. Results also reveal that utilitarian products are more affected by the presence of one warning and in the case of these products these differences disappear when the number of warnings increases.